Identifikasi Makroskopis dan Mikroskopis Kayu Medang Sereh Berdasarkan Bagian Batang : Macroscopic and Microscopic Identification of Lemongrass Medang Wood Based on Stem Section - Anggraini, Riana; Agustina, Ana; Komariah, Rahma Nur; Khabibi, Jauhar (Jurnal Silva Tropika, 2023)
ABSTRACT Some aspects that can be a reference in identifying lemongrass wood include anatomical structure (macro and micro properties) based on the trunk (base, middle and end). The results of research identifying the anatomical properties of lemongrass wood on various parts of the trunk provide conclusions of anatomical structure for the macroscopic structure characteristics of lemongrass wood in general do not differ between the position of the base, middle and end and the terrace and sapwood, namely giving the heartwood color brown, has a striped pattern, a rather smooth texture, a smooth tactile effect, somewhat shiny, has a smell like lemongrass or telon oil, the hardness is rather hard and heavy. The microscopic structural characteristics of lemongrass medang wood in the position of lemongrass medang logs (base, middle and tip) show that in general wood fibers experience an increase in length from pith to leather. Based on testing the quality of wood fiber for pulp and paper use which includes fiber length, Runkle Ratio, Muhlstep Ratio (MR), Felting Power (FP), Flexibility Ratio (FR) and Coefficient of Rigidity (CR) that lemongrass wood fiber is included in quality class III. Quality class III is a class of wood fiber that has tear firmness, rupture resistance and low tensile firmness.   Keywords: macroscopic, microscopic, medang wood, position of the trunk   ABSTRAK Beberapa aspek yang dapat menjadi acuan dalam mengidentifikasi kayu medang sereh ini adalah meliputi struktur anatomi (sifat makro dan mikro) berdasarkan bagian batangnya (pangkal, tengah dan ujung). Hasil penelitian identifikasi sifat anatomi kayu medang sereh pada berbagai bagian batang memberikan kesimpulan struktur anatomi untuk ciri struktur makroskopis kayu medang sereh secara umum tidak berbeda antara posisi pangkal, tengah dan ujung dan bagian teras dan gubalnya yaitu memberikan warna kayu terasnya coklat, mempunyai corak bergaris-garis, tekstur agak halus, kesan raba halus, agak mengkilap, mempunyai bau seperti bau sereh atau minyak telon, kekerasan agak keras dan berat. Â Ciri struktur mikroskopis kayu medang sereh secara pada posisi batang kayu medang sereh (pangkal, tengah dan ujung) menunjukkan bahwa secara umum serat kayu mengalami penambahan panjang dari empulur hingga menuju kulit. Berdasarkan pengujian kualitas serat kayu untuk penggunaan pulp dan kertas yang meliputi panjang serat, Runkle Ratio, Muhlstep Ratio (MR), Felting Power (FP), Flexibility Ratio (FR) dan Coeffisien of Rigidity (CR) bahwa serat kayu medang sereh masuk ke dalam kelas mutu III. Kelas mutu III merupakan kelas serat kayu yang memiliki keteguhan sobek, ketahanan pecah dan keteguhan tarik yang rendah.   Kata kunci: medang sereh, posisi batang, makroskopis, mikroskopis